P2-S2.18 Are we doing enough to cover risk of STI/HIV transmission from the lovers "of female sex workers (FSWs)?". (10th July 2011) - Doddamane, M; Bhattacharjee, P; Rao, D
Abstract : Background: Condoms use among Female sex workers with paid clients found to have increased rapidly in three years from 58% to 76% (IBBA data) due to scale up of interventions among them. However condom use with lovers still remains low at 33% (IBBA 2008). PBS 2009 shows 50% of the sex workers have lovers. Programmatically it has been challenging to design and implement programme to reach out to Lovers and to provide them services consistently. To understand the Lovers and the risk factor associated with them we conducted Focused Group Discussion (FGDs). Method: 14 Separate FGDs were conducted with both the FSWs and their Lovers in seven districts of Karnataka. A structured tool guided the Facilitators of the FGD. Each FGD was documented by a Recorder. Results: Three fourths of the FSWs had more than one lover at any given point of time. One fourth of the lovers had physical relationship with other FSWS or women other than wife. Half of the FSWs especially the urban based changed lovers in less than a year. Majority of the lovers knew that their partner is a sex worker. Key barriers for Lovers to use condoms with the sex workers were: 1. Faith and trust with FSWs (almost half of the respondents) 2. Condoms don't give pleasure (one third of the respondents). The barriers stated by the FSWs were: 1. Faith and trust in the lover because they are like husbands (one third of the respondents) 2. Did not want to make the lover suspicious (one fourth of the respondents) One fourth of the sex workers responded experiencing harassment from the lovers especially for money. Only one third of the lovers had correct information about HIV (modes of transmission) and negligible number of lovers accessed STI services. Conclusion: Evidence shows that there is clear need to intervene with Lovers of female sex workers to improve condom use among them. The interventions have to address not only gaps in information, condom use, access to service, but also the perception of faith and trust.